Mineração de dados educacionais na identificação do perfil dos egressos para apoio à gestão educacional de escola técnica pública - Andrelo, Pamela Ferreira Alves (2022)
The Public Technical Schools of the State of São Paulo, acronym in portuguese language ETECS have sought improvements aimed at the training of their students, through the analysis of data from their graduates who passed the entrance exam, to support educational management in the development of education strategies, with a view to passing these exams and being placed in a job vacancy. The performance of these graduates can be analyzed with the application of Educational Data Mining (EDM). The general objective of this work was to identify and analyze the profile of graduates from public technical schools who passed the entrance exam, using Educational Data Mining to implement changes that support educational management in the development of educational strategies. ETEC Paulistano, object of study of this work, has a student body composed of 95% of students from the Vila Brasilândia region, 70% of them coming from the municipal public school. Three questionnaires were applied to the graduates of the classes from 2016 to 2018, 2019 and 2020. To mine the results, five steps were applied, based on the phases of the Knowledge Discovery in Databases (KDD) process: Selection and Data Collection; Data Pre-Processing; Educational Data Mining; Interpreting and Analyzing Discovered Knowledge and Implementing Changes. The identification of the graduate's profile made it possible to implement changes based on the analysis of the results of the questionnaire for the years 2016 to 2018, resulting in the creation of two new courses and a reduction in the daily workload of the courses from 8 to 6 hours; predict the implementation of changes based on the analysis of the results of the questionnaires for the years 2019 and 2020, highlighting the need for training course coordinators and teachers and practical classes requested by the environment class, among others; and consider implementing changes that can be made based on the analysis of the results of the 2019 and 2020 questionnaires, such as technical visits to companies and workshops with professionals in the area, among others. It was concluded, then, that EDM enabled the implementation of changes, which subsidized educational management in the development of educational strategies.